2008
DOI: 10.1186/1471-2148-8-61
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of gastropod mitochondrial genome arrangements

Abstract: BackgroundGastropod mitochondrial genomes exhibit an unusually great variety of gene orders compared to other metazoan mitochondrial genome such as e.g those of vertebrates. Hence, gastropod mitochondrial genomes constitute a good model system to study patterns, rates, and mechanisms of mitochondrial genome rearrangement. However, this kind of evolutionary comparative analysis requires a robust phylogenetic framework of the group under study, which has been elusive so far for gastropods in spite of the efforts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
193
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(234 citation statements)
references
References 77 publications
(115 reference statements)
28
193
0
3
Order By: Relevance
“…In this study, we investigated complete protein-coding genes of 32 published gastropod species that produced 4044 length of alignable amino acids sequences. Most of the phylogenetic clades shown in the present study matched with the recent taxonomy and phylogeny of Gastropoda (Bouchet and Rocroi, 2005;Grande et al, 2008), although a bit opposite to the traditional subclasses of Gastropoda (i.e., Prosobranchia, Opisthobranchia, and Pulmonata), which was already discussed well by Grande et al (2008) and may be just beyond the topic of the present study. However, some questions still remain regarding the relationship of Caenogastropoda and Heterobranchia, two of which were thought as sister groups comprising the Apogastropoda; but in the present study, Vetigastropoda showed a closer relationship with Caenogastropoda than Heterobranchia.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In this study, we investigated complete protein-coding genes of 32 published gastropod species that produced 4044 length of alignable amino acids sequences. Most of the phylogenetic clades shown in the present study matched with the recent taxonomy and phylogeny of Gastropoda (Bouchet and Rocroi, 2005;Grande et al, 2008), although a bit opposite to the traditional subclasses of Gastropoda (i.e., Prosobranchia, Opisthobranchia, and Pulmonata), which was already discussed well by Grande et al (2008) and may be just beyond the topic of the present study. However, some questions still remain regarding the relationship of Caenogastropoda and Heterobranchia, two of which were thought as sister groups comprising the Apogastropoda; but in the present study, Vetigastropoda showed a closer relationship with Caenogastropoda than Heterobranchia.…”
Section: Discussionsupporting
confidence: 87%
“…The species within the Gastropoda were identified into four main lineages: Caenogastropoda, Vetigastropoda, Patellogastropoda and Heterobranchia. Within the Heterobranchia, both Pulmonata and Opisthobranchia were recovered to be polyphyletic, and P. dolabrata in the Pyramidelloidea was recovered deep within Pulmonata and Opistobranchia, which is coincident with the Gastropoda phylogentic tree constructed by Grande et al (2008). The interrelationship within Caenogastropoda matches their published taxonomy, except that C. parthenopeum is more closely related to Neogastropoda than to Littorinimorpha.…”
Section: Phylogenetic Analysis Of Amino Acid Sequencessupporting
confidence: 53%
See 2 more Smart Citations
“…The two most comprehensive data sets thus far for euthyneuran (opisthobranch and pulmonate) phylogenetics have been published by Grande et al (2008), based on mitochondrial genomes, and by Klussmann-Kolb et al (2008), based on 18S, 28S, 16S, and COI data. Dinapoli and Klussmann-Kolb (2010) also published a study focusing on early heterobranchs, i.e., the lineages that branched off just before euthyneurans.…”
Section: Introductionmentioning
confidence: 99%